The Patterns and Determinants of Agricultural Credit Use among Farm Households in Oyo State, Nigeria - Adekoya, O. A (Asian Economic and Financial Review, 2014)
The study examined the patterns and determinants of agricultural credit use among farming households in Oyo State, Nigeria. The primary data used for the study were obtained from a cross sectional survey of 114 farm households drawn by multi-stage random sampling technique. Both descriptive statistics and multiple regressions were used to analyze the data obtained. The study revealed that 47.4% of farm households in the State were in the age bracket of 51-60 years with mean age of 58 years while majority (86.8%) were farmers. Also, 48.2% had no formal education and 22.8% had between 7-12 years of formal education. Over half of the farm households (58%) maintained a household size of 5 – 8 with mean size of five while 27.2% and 26.3% had between 11-20 years and 21-30 years of farming experience. In addition, 52% of the respondents in the State patronized the cooperative societies with mean loan requested as ₦108,157.89, mean loan released as ₦97,763.15 and mean loan repaid being ₦70,898.24. The major constraints faced by the rural farm households in accessing loans include high interest rate (21.9%) and lack of collateral (14.9%). Farm size (p<0.01), membership of a social organization (p<0.01), number of adult males in households (p<0.01) and off farm income (p<0.05) had positive significant influence on the amount of credit the household can secure. The adjusted R2 of 60.7% indicates that 60.7% of the variations in the amount of credit/loan obtained were explained by the specified variables in the model. The study recommends that government should organize, strengthen and harmonize the activities of the various cooperative societies with the aim of making them more effective in microcredit utilization.